2011
DOI: 10.1088/1674-4527/11/12/005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Newtonian dynamics for rotation curve analysis of thin-disk galaxies

Abstract: We present an efficient, robust computational method for modeling the Newtonian dynamics for rotation curve analysis of thin-disk galaxies. With appropriate mathematical treatments, the apparent numerical difficulties associated with singularities in computing elliptic integrals are completely removed. Using a boundary element discretization procedure, the governing equations are transformed into a linear algebra matrix equation that can be solved by straightforward Gauss elimination in one step without furthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…The rotational velocity v(r) with a maximum rotation velocity V max can have several functional forms: it can be an arctan velocity profile (e.g. Puech et al 2008), an inverted exponential (Feng & Gallo 2011), or a hyperbolic tanh profile (e.g. Andersen & Bershady 2013) :…”
Section: A Parametric Galaxy Model In Three Dimensionsmentioning
confidence: 99%
“…The rotational velocity v(r) with a maximum rotation velocity V max can have several functional forms: it can be an arctan velocity profile (e.g. Puech et al 2008), an inverted exponential (Feng & Gallo 2011), or a hyperbolic tanh profile (e.g. Andersen & Bershady 2013) :…”
Section: A Parametric Galaxy Model In Three Dimensionsmentioning
confidence: 99%
“…It was proved long time ago (Kuzmin 1952(Kuzmin , 1955 that there is no evidence for the presence of large amounts dark matter in the disk of the Galaxy from observations in the solar neighborhood, and this is still confirmed today (Garbari et al 2012), but one might investigate whether amounts of dark matter in the outer disk are possible. From the theoretical point of view at least, it is a general solution A128, page 8 of 9 for the observed rotation curves : Feng & Gallo (2011) showed that some mass distributions of the disk alone might mimic the flat rotation curves of a galaxy (Mestel's disk), without dark matter halos, although these distributions are not realistic compared with the observed stellar distribution (exponential).…”
Section: Dynamical Consequencesmentioning
confidence: 99%
“…where V (r) is measured in units of a characteristic rotational velocity V 0 . As shown in our previous publications (Gallo and Feng, 2009, Feng and Gallo, 2011, 2014, equating (3) and (4) with slight algebraic arrangements yields a force-balance equation,…”
Section: Mass In a Galaxymentioning
confidence: 88%